Nigella Sativa - an ordinary herb or a miraculous medicine? - Jakub Orczyk; Aleksandra Ołownia; Agata Tokarzewska; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2023)
Nowadays, herbal preparations are increasingly used in medicine. These preparations are cheaper, more available and they have fewer side effects than synthetic ones. Nigella Sativa, commonly known as Black Cumin, has been used in traditional medicine since antiquity. This herb is known to have many properties. The prophet Muhammad himself has already mentioned them, claiming that "Black Cumin is a cure for all diseases except death". Researches on N. Sativa confirmed that it has anti-diabetic, anti-asthmatic, pro-fertility, antioxidant, hepatoprotective, neuroprotective, gastroprotective, immunomodulatory, analgesic, antibacterial, anti-inflammatory and anti-ischemic effects. Many of these properties are due to thymoquinone, which is the main component of black cumin essential oil. This present review is an attempt to provide a specific overview of researches and literatures of pharmacognostical profile and pharmacological activity of the seeds of this plant. It will be helpful for scientists, researchers and other healthcare professionals, who are working with this plant and who need to be up to date about it.